Do Organizational Support and Work Environment Enhance Workplace Happiness? Evidence from Indonesian Social Rehabilitation Employees - Diana Anggelia; Dedi Muhammad Siddiq; Dede Nurdin; Maheran Zakaria (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2026)
Purpose: This study examines the effects of perceived organizational support and the work environment on workplace happiness, with job satisfaction serving as a mediating variable among employees of a public social rehabilitation institution in Indonesia.Method: A quantitative research design was employed using survey data collected from 200 employees of the Wyata Guna Center in Bandung, Indonesia. Data were obtained through a structured questionnaire based on a five-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0.Result: The findings show that perceived organizational support and the work environment have significant and positive effects on both job satisfaction and workplace happiness. Furthermore, job satisfaction significantly mediates the relationships between perceived organizational support, the work environment, and workplace happiness. These findings suggest that supportive organizational practices and conducive working conditions enhance employees’ psychological well-being by increasing job satisfaction.Practical Implications for Economic Growth and Development: Strengthening organizational support and fostering a positive work environment can improve employee happiness, job satisfaction, and productivity. Higher levels of employee well-being may contribute to better service quality, greater institutional efficiency, and more effective use of public resources. These improvements support sustainable human capital development in the public sector and strengthen the capacity of public institutions to deliver services that contribute to long-term socio-economic development.Originality/Value: This study offers empirical evidence from an Indonesian public social service institution and highlights job satisfaction as a key psychological mechanism linking perceived organizational support and the work environment to workplace happiness.